Contributions to the fungal diversity of the Cerrado: new records of lignocellulolytic Agaricomycetes - Regio, Nicolas do Carmo; Palacio, Melissa; Westphalen, Mauro Carpes; Feuerstein, Shirley Cunha; Silveira, Rosa Mara Borges da (Iheringia, Série Botânica., 2024)
The Cerrado biome is considered a biodiversity hotspot. Nevertheless, it has one of the least known fungal diversities in Brazil. In order to increase knowledge of its diversity and distribution, samples were collected, in September of 2018, from three national conservation parks and one private property covering Cerrado regions in the states of Minas Gerais, Goiás, Tocantins and Maranhão. 53 specimens were identified, comprehending 37 species from 12 families and five orders of Agaricomycetes. Nine species are new records for the Cerrado and, amongst them, Perenniporiella tepeitensis is also a new record for Brazil. Brief descriptions and taxonomic issues of each species are presented, and knowledge of fungal diversity in the four states increased considerably.